Depicting the Work of Police Foundations on Social Media: A Visual Communication Analysis - Dolamore, Stephanie; Sowa, Jessica E.; Edwards, Lauren Hamilton (Journal of public and nonprofit affairs, 2022)
Visual imagery is a fundamental element of our communication systems. Unlike spoken or written words that deliver meaning one word at a time, images convey multiple messages instantly with powerful impact. This study explores the content embedded in the social media images used by nonprofit police foundations in the United States through archeological visual analysis. Findings reveal that public service organizations navigate curation choices when selecting images for social media accounts, such as how best to depict the mission of the organization. The prioritization of image curation is imperative, especially with the growth of social media as a space for promoting encounters with, not just information distribution to, citizens. In the public service, the importance of image curation lies in the potential to reinforce the work of organizations, but the risk is miscommunication with consequences for public trust.